Design of the Container for the Sampling and Detection Monitoring System of N-13 in Pressurized Water Reactor Primary Loop Water Leakage Based on the Coincidence Method - Zhao, Yue; Qu, Guo-Pu; Zhou, Jian-Liang (Frontiers in Energy Research, 2019)
The N-13 coincidence method is an effective approach for monitoring the primary loop leakage in pressurized water reactors. The high coincidence efficiency and low background are crucial to achieving a lower limit of measurement for such a monitoring system. In this paper, we proposed four types of geometric designs of the sampling composing NaI(TI) detector. For varying container volumes (V), the detection efficiency (ε) of these containers was investigated through the Geant4 simulation and experimental measurement. The value of ε•V, which is a key combined parameter, was obtained accordingly. Finally, we obtained the optimal size of the suitable sampling and detection container for the coincidence method.